First order dominance analysis: Child wellbeing in the Democratic Republic of Congo - Malokele Nanivazo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper performs a multidimensional first order dominance (FOD) analysis of child wellbeing in the Democratic Republic of Congo (DRC). This methodology allows the ordinal ranking of the 11 provinces of the DRC in terms of their wellbeing based upon the probability of their domination. This empirical application obviates the need to adopt a weighting scheme for the deprivation indicators or to rely on the signs of other cross-derivatives for comparison. I execute a bootstrap linear programming algorithm on seven deprivation indicators for three sub-samples of children derived from the DRC 2007 Standard Demographic and Health Survey. The results reveal widespread disparities in child wellbeing in the DRC.
Keywords: C81; I32; J13; 330; welfare; first order dominance; Democratic Republic of Congo; multidimensional poverty